Designing Population Data Information System in Cipta Asri Housing, Sagulung Village: Perancangan Sistem Informasi Data Kependudukan Pada Perumahan Cipta Asri Kelurahan Sagulung - Evan Rosiska; Very karnadi (Perkumpulan Doktor Indonesia Maju (PDIM), 2020)
The more advanced information technology today, the need for a computerized information system has covered all fields such as RT (Neighborhood Association) and RW (Community Housing). The survey shows that 30% of the process of documenting digital data citizens have used a computerized system without the support of a database system, where documentation uses Microsoft Word and Microsoft Excel. Every new citizen has to report data such as National Identity Card and Family Card, then the operator will record the data in a book, then save the data into Microsoft Word or Microsoft Excel. Every citizen who will make a certificate must fill out the form provided. This makes the population service process less effective. With the processing of population data using computerized techniques with a database system, digital data documentation of citizens will be easier to find data, the quality of service citizens who want to do correspondence become faster in terms of time, and the process of making population reports more effective